Biology and Management of Pusley (Richardia L.) in Tomato, Pepper, Cucurbit, and Strawberry Production - Shaun M. Sharpe; N. S. Boyd; Chris Marble; Shawn Steed (EDIS)
Four species of pusley (Richardia L.) are widespread and common weeds in Florida vegetable and strawberry production. We refer to the native plant Richardia scabra L. as Florida pusley. This discrimination is necessary because these species are often referred to collectively as Florida pusley due to overlapping distributions, similar growth habits and leaf morphologies, and difficulty identifying without the presence of fruit. This new 6-page publication of the UF/IFAS Horticultural Sciences Department describes the different pusley species and provides management options for strawberry, pepper, cucurbits, and tomato. Written by Shaun M. Sharpe, Nathan S. Boyd, Chris Marble, and Shawn Steed. https://edis.ifas.ufl.edu/hs1331